Dampak Faktor Demografi Terhadap Keputusan Investasi Pada Pelaku Bisnis Franchise di Kota Samarinda - Muhammad Rizal Sapriansyah; Justina Ade; Muhammad Amin Kadafi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This research was aims to know the correlation of demographic factors on investment decision of franchise business in samarinda. Data in this research was obtained by distributing questionnaire to owner of franchise business who found by researcher. The sample of paper was collected using a purposive sampling with determined criteria. Then the data was analyzed using crosstabulation and chi-square analysis. The result of this study found that demographic factors have correlation on investment decision of franchise business in samarinda. Out of seven demographic factors observed, there were six factors have correlation on investment decision. The factors were gender, age, marital status, occupation, last education and investment experience. However, there one factor that have not correlation on investment decision i.e. ethnic